APIR: methodology for risk assessment and prioritization in HACCP plans (UNED Research Journal, 2022)
Introduction: A prioritization methodology based on bottom-up risks is proposed for different hazards and food matrices. The variables of the model are subdivided into two categories: a) the characteristics of the hazard, where the probability of occurrence and severity are quantified. (b) the properties of the food matrix which estimate its epidemiological risk, presence in the food and vulnerability of its manufacture. A Risk Index (IR) is established as a parameter to facilitate food safety managers to discriminate and prioritize Significant Hazards during the hazard identification of HACCP plans. Objective: The aim of this work was to establish a flexible and dynamic methodology of prioritization based on risk for processing and processing companies of animal products intended for human consumption and integrate it with HACCP plans, allowing specific controls to be established in the production process. Results: The significance values between the clusters Nrp and Nrm were p